Overexpression of Foxc1 regenerates crushed rat facial nerves by promoting Schwann cells migration via the Wnt/β‐catenin signaling pathway. Issue 12 (11th May 2020) - Xia, Wenzheng; Zhu, Jin; Wang, Xueyi; Tang, Yinda; Zhou, Ping; Wei, Xiangyu; Chang, Bowen; Zheng, Xuan; Zhu, Wanchun; Hou, Meng; Li, Shiting
Abstract: Facial paralysis can result in severe implications for patients. A good prognosis depends on the degree of nerve regeneration. Schwann cells (SCs) play an important role in facial nerve development and regeneration through migration. Forkhead box C1 (Foxc1), a member of the forkhead transcription factor family, is implicated in cell migration. However, the role of Foxc1 in the progression after facial nerve crush remains unknown. Our aim was to evaluate the effect of Foxc1 overexpression on SC migration and recovery of facial nerves after crush injury. The rat facial nerve crush injury model was established through the use of unilateral surgery. The results showed that the expression of Foxc1 was increased in the surgery group compared to that of the control group. SCs were isolated from the sciatic nerves and cultured. Foxc1, delivered by an adeno‐associated virus in vivo, or adenovirus in vitro, both induced overexpression of Foxc1, and increased the expression of CXCL12 and β‐catenin. After the transfection of Foxc1, the migration of SC was increased both in vitro and in vivo, was reduced by the inhibition of CXCL12 or β‐catenin. The facial nerve function and the nerve axon remyelination of the rats transfected with Foxc1 were significantly improved after nerve crush injury. Overall, the results demonstrated that overexpression of Foxc1 promoted SC migration by regulating CXCL12 via the Wnt/β‐catenin pathway, thus contributing to improved facial nerve function after crush injury. Abstract : In this study, we described our novel finding that the overexpression of Forkhead box C1 promoted Schwann cell migration via the Wnt/β‐catenin pathway to improve facial function after nerve crush injury. Our findings may lead to new treatment strategies for facial nerve injury.